Glycotargeted therapeutic agents - HUBBELL JEFFREY A; WILSON DAVID SCOTT (2024)
The present invention relates to glycotargeted therapeutic agents. Some embodiments of the invention relate to therapeutic compositions configured to target the liver of a subject and may be used to treat or prevent one or more of graft rejection, autoimmune disease, food allergy, and an immune response against a therapeutic agent. In some embodiments, the compositions are configured to target the liver and deliver antigens that are desirable to tolerate. In some embodiments, the compositions are configured for clearing circulating proteins or peptides or antibodies associated with one or more diseases mentioned above. Also disclosed herein are methods and uses of the compositions for inducing immune tolerance. 本发明涉及糖靶向治疗剂。本发明的一些实施方案涉及治疗性组合物，其配置为靶向受试者的肝并且可用于治疗或预防移植物排斥、自身免疫性疾病、食物变态反应、和针对治疗剂的免疫应答中的一种或多种。在一些实施方案中，组合物配置为靶向肝，并且递送期望耐受的抗原。在一些实施方案中，组合物配置为用于清除与一种或多种上文提及的疾病有关的循环蛋白或肽或抗体。本发明中还公开用于诱导免疫耐受性的组合物的方法和用途。